MORPHOLOGICAL CHANGES OF TEETH’s GERMS OF MISE’s EMBRYOS OF UNDER ACT OF CHOLESTEROL - Yakubova, I.I.; Tumanovskaya, L.V.; Каськова, Л.Ф. (World of Medicine and Biology, 2012)
In an experiment on preparations of teeth’s germs of 17-days embryos of mise, which during pregnancy got a cholesterol considerable morphological changes which testify to the expressed functional disfunction of ameloblasts and odontoblasts are educed.